1997
DOI: 10.1016/s0022-5347(01)64139-9
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Assessment of Patients With Acute Urinary Retention: Is Treatment Failure After Prostatectomy Predictable?

Abstract: Patients with acute urinary retention, age 80 years or older, with retention volume greater than 1,500 ml., no evidence of instability and maximal detrusor pressure less than 28 cm. water are at high risk of treatment failure. However, despite treatment failure the detrusor may recover in patients younger than 80. Therefore, prostatectomy should still be performed in this group (less than 80 years old) even if preoperative urodynamics suggest an unfavorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 17 publications
7
62
0
Order By: Relevance
“…Several factors were associated with failure, i.e. being older than 75 years, a drained volume of >1000 mL and a detrusor contraction of <35 cmH 2 O [58].…”
Section: A Trial Without Cathetermentioning
confidence: 99%
“…Several factors were associated with failure, i.e. being older than 75 years, a drained volume of >1000 mL and a detrusor contraction of <35 cmH 2 O [58].…”
Section: A Trial Without Cathetermentioning
confidence: 99%
“…Continuous urinary drainage through catheter bypasses the BOO, keeps bladder in collapse state and provides rest to DM [35][36][37][38][39]. UDS is the gold standard for measuring detrusor contractile dysfunction and quantitating the degree of BOO [14,[40][41][42][43][44][45][46].…”
Section: Neurological Diseasementioning
confidence: 99%
“…All these studies directly or indirectly indicate that more the duration, more the chance of detrusor damaged in CUR due to BOO. Bob Djavan et al [46] reviewed that patients with age more than 80 years, residual urine of more than 1000 ml and initial voiding detrusor pressure less than 28 cm H2O on presentation was associated with less chances of detrusor recovery after relieving the BOO.…”
Section: Neurological Diseasementioning
confidence: 99%
“…While some have found no difference in success rates at 24 and 48 h, 32 others have suggested a benefit to waiting longer, particularly in men with large residual volumes 41 l. 33 It has recently been suggested that prostate size 427.5 g, residual volume 41 l and age 475 y may reduce the chance of successfully voiding after a TWOC. 34 It has also been suggested that the use of an alpha blocker may improve the success rate of a TWOC.…”
Section: Treatment Catheterisationmentioning
confidence: 99%
“…55 Urodynamic evaluation has not been shown to predict this in patients under the age of 80 y as detrusor failure may recover postoperatively. 33 Therefore, urodynamics are not recommended for routine preoperative evaluation in this age group. The presence of residual volume 41500 ml, lack of detrusor instability, detrusor pressure at maximum fill of o9 cm water and maximal detrusor pressure o28 cm water were all found to predict treatment failure.…”
Section: Surgical Interventionmentioning
confidence: 99%